Mitochondrial Multiorgan Disorder Syndrome (Mimods) Due To Mutations In The Slc25a46 Gene - Finsterer, MD, PhD, Josef; Zarrouk-Mahjoub, PhD, Sinda (Journal of Medical Biomedical and Applied Sciences, 2018)
In a recent article, Braunisch et al. reported about 4 patients(VI-5, VI-4, II-3, II-4) with pontocerebellar hypoplasia(PCH) due to mutations in the SLC25A46 gene1. We havethe following comments and concerns